MISTERY BOX SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF KOMPETENSI SIKLUS AKUNTANSI PERUSAHAAN DAGANG - DIAH ARUMSASI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
Conventional learning tends to be teacher-centered, making learning monotonous and boring, students are not active and lazy so that student understanding becomes low. The use of the right media can be a stimulus for students to be more enthusiastic in participating in the teaching and learning process. This requires creative ideas from the teacher as a designer and implementer of learning scenarios in the classroom. The purpose of this study is to find out whether the Problem Base Learning Model can improve students' understanding and mastery of the concept of the Trading Company Accounting Cycle. This Best Practice also uses recycled materials in the form of cardboard which is formed as a medium called "Mystery Box" to provide illustrations and simulations to students regarding trading company materials. The "Mystery Box" was carried out in the learning process as well as the Lesson Study program which was carried out together with the observation and assistance of the 2013 Curriculum Team from the LPMP Central Java Province and the Demak Regency Senior High School supervisor at SMA Negeri 2 Mranggen Class XII IPS 5 on the material of the Accounting Cycle of Trading Companies in 2018 is expected to have a positive impact on the teaching and learning process as well as schools and teachers of the 2013 Curriculum Implementation model. ABSTRAK Pembelajaran konvensional cenderung berpusat pada guru menjadikan pembelajaran monoton dan membosankan, siswa tidak aktif dan malas sehingga pemahaman siswa menjadi rendah. Pemakaian Media yang tepat mampu menjadi stimulus bagi siswa untuk lebih antusias dalam mengikuti proses belajar mengajar. Hal ini memerlukan ide kreatif dari guru sebagai perancang dan pelaksana skenario pembelajaran di kelas.Tujuan penelitian ini adalah Mengetahui apakah Model Pembelajaran Problem Base Learning dapat meningkatkan pemahaman dan penguasaan siswa mengenai konsep Siklus Akuntansi Perusahaan dagang. Dalam Best Practise ini juga menggunakan bahan daur ulang berupa Kardus yang dibentuk sebagai media bernama “Mistery Box” untuk memberikan ilustrasi dan simulasi kepada siswa mengenai materi perusahaan dagang. “Mistery Box” yang dilakukan pada proses pembelajaran sekaligus program Lesson Study yang dilaksanakan bersama dengan observasi dan pendampingan Tim Kurikulum 2013 dari LPMP Propinsi Jawa Tengah dan pengawas SMA Kabupaten Demak di SMA Negeri 2 Mranggen Kelas XII IPS 5 pada materi Siklus Akuntansi Perusahaan Dagang pada tahun 2018 diharapkan mampu memberi dampak positif dalam proses belajar mengajar sekaligus sebagai sekolah dan guru model Implementasi Kurikulum 2013.